MALARIA KNOWLESI PADA MANUSIA - Patricia Angelika; Felicia Kurniawan; Bryany Titi Santi (Bahasa Indonesia, 2021)
Introduction: Plasmodium knowlesi is a malaria agent that initially only infected monkeys, Macaca fascicularis and Macaca nemestrina. P. knowlesi has developed to infect zoonotically by transmitting from animals to humans by the female Anopheles vector. Since the first endemic incidence of knowlesi malaria in 2004 in Sarawak, Malaysia, the number of its infection cases has expanded to almost all regions in Southeast Asia, including Indonesia. The P. knowlesi infection cases increase results from complex interactions between humans, agents, and environment. Individual and environmental factors are risk factors for knowlesi malaria. The life cycle of P. knowlesi is concise and tends to infect all erythrocyte types along with other Plasmodium species. The P. knowlesi morphology and clinical features are very similar to the other Plasmodium species, making them difficult to differentiate and contributing to the increase in infection cases. Presently, the knowlesi malaria molecular PCR diagnosis technique is the most accurate method. Immediate treatment is needed to prevent severe malaria and death. Objective: This article aims to study epidemiology, risk factors, life cycle, morphology, clinical symptoms, diagnosis, and the latest management of knowlesi malaria cases, especially in Indonesia. Method: Writing articles used a literature review method from various literature on knowlesi malaria. Discussion: Knowledge of epidemiology, risk factors, life cycle, morphology, clinical symptoms, diagnosis, and management of malaria cases can add information to the development of research on the distribution and control of knowlesi malaria. This article can help accelerate the target of malaria elimination in Indonesia by 2030.